(untitled) (Educational Perspectives Magazine (REPED), 2022)
The following text is about self-assessment processes in the context of Early Practicum of the 2005 class of the Playa Ancha University Basic Education Pedagogy careen Self-assessment is recognized as a mean of specifying the reflexive processes described in the Professional Profile necessary for professional training. Some selfassessment description instruments for several stages of the Early Practicum (VISE) are analysed.